Hemato-lymphoid in vivo reconstitution potential of subpopulations derived from in vitro differentiated embryonic stem cells - Potocnik, Alexandre J. (The National Academy of Sciences of the USA, 1997)
During differentiation in vitro, embryonic stem (ES) cells generate progenitors for most hemato-lymphoid lineages. We studied the developmental potential of two ES cell subpopulations that share the fetal stem cell antigen AA4.1 but differ in expression of the lymphoid marker B220 (CD45R). Upon transfer into lymphoid deficient mice, the B220(+) population generated a single transient wave of IgM(+) IgD(+) B cells but failed to generate T cells. In contrast, transfer of the B220(−) fraction achieved long-term repopulation of both T and B lymphoid compartments and restored humoral and cell-mediated immune reactions in the recipients. To assess the hemato-lymphopoietic potential of ES cell subsets in comparison to their physiological counterparts, cotransplantation experiments with phenotypically homologous subsets of fetal liver cells were performed, revealing a more potent developmental capacity of the latter. The results suggest that multipotential and lineage-committed lymphoid precursors are generated during in vitro differentiation of ES cells and that both subsets can undergo complete final maturation in vivo.